Leveraging Artificial Intelligence and Technology for Enhancing Halal Supply Chain Management - Ghalih, Muhammad; Chang, Chia Hua; Safitri, Yulita Dwi (Universitas Negeri Padang, 2025)
Halal Supply Chain Management (HSCM) is transforming the way halal products are certified, tracked, and distributed. However, challenges such as regulatory compliance, technological readiness, cost, and stakeholder trust continue to impact AI adoption in the halal industry. This study employs the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method to analyze the causal relationships among key factors influencing AI adoption in halal supply chains. Seven key criteria were identified: Technological Infrastructure, Regulatory Compliance, Cost of Implementation, Data Security & Privacy, Scalability & Adaptability, Stakeholder Readiness, and Consumer Trust & Perception. The findings reveal that Technological Infrastructure is the most influential factor driving AI adoption, impacting Regulatory Compliance, Scalability, and Consumer Trust. Conversely, Consumer Trust & Perception emerged as the most dependent factor, highlighting the importance of transparency in AI-based halal certification. Regulatory Compliance plays a dual role as both a cause and an effect, emphasizing the need for standardized AI-driven halal certification frameworks. The results suggest that investment in AI-driven traceability, blockchain-based halal authentication, and automated compliance verification can significantly improve halal supply chain efficiency and consumer confidence. This study provides valuable insights for policymakers, halal certification bodies, and industry stakeholders by identifying key enablers and barriers to AI adoption. Future research should explore hybrid Multi-Criteria Decision-Making (MCDM) approaches, economic feasibility analyses, and real-world case studies to further validate AI-driven solutions in halal supply chains.